Volume 1A: Aircraft Engine; Fans and Blowers 2014
DOI: 10.1115/gt2014-26369
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Short Nacelles for Low Fan Pressure Ratio Propulsors

Abstract: This thesis addresses the uncharted inlet and nacelle design space for low pressure ratio fans for advanced aeroengines. A key feature in low fan pressure ratio (FPR) propulsors with short inlets and nacelles is the increased coupling between fan and inlet. The thesis presents an integrated fan-nacelle design framework, combining a spline-based tool for the definition of inlet and nacelle surfaces with a fast and reliable body-force-based approach for the fan rotor and stator blade rows. The new capability cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…In general, about 100,000 iterations were required to reach a settled unsteady flow solution. Details on the nacelle design framework, the meshing strategy, the computational setup of the URANS calculations, and the results of grid convergence studies can be found in [14].…”
Section: Inlet and Nacelle Design Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, about 100,000 iterations were required to reach a settled unsteady flow solution. Details on the nacelle design framework, the meshing strategy, the computational setup of the URANS calculations, and the results of grid convergence studies can be found in [14].…”
Section: Inlet and Nacelle Design Methodsmentioning
confidence: 99%
“…However, that same outward shift in the stagnation point exacerbates the over-speed along the inlet internal surface at low-speed conditions, resulting in increased rotor incidence distortion levels. A detailed assessment of unconventional spinner shapes is given in [14]. The short-inlet propulsors discussed in this paper feature conventional spinner designs similar to the shape included in the baseline configuration, as shown for example at the top in Fig.…”
Section: Short-inlet Design Strategymentioning
confidence: 99%
See 3 more Smart Citations